2022
DOI: 10.1002/wics.1599
|View full text |Cite
|
Sign up to set email alerts
|

A review of recent advances in empirical likelihood

Abstract: Empirical likelihood is widely used in many statistical problems. In this article, we provide a review of the empirical likelihood method, due to its significant development in recent years. Since the introduction of empirical likelihood, variants of empirical likelihood have been proposed, and the applications of empirical likelihood in high dimensions have also been studied. It is necessary to summarize the new development of empirical likelihood. In this article, we give a review of the Bayesian empirical l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 176 publications
0
7
0
Order By: Relevance
“…It is worth noting that the nonparametric log-likelihood ratio in (5), coincides with the log-likelihood ratio based on the (independent) binomial distributions of F1 (t 1 ), P2 (t 1 , t 2 ) and F3 (t 2 ). This provides a further justification for the result in Theorem 2.1 under the considered weak conditions, which do not even involve the continuity of F 1 , F 2 and F 3 .…”
Section: Three-sample El and Confidence Regions For Triplets Of Tcfsmentioning
confidence: 68%
See 2 more Smart Citations
“…It is worth noting that the nonparametric log-likelihood ratio in (5), coincides with the log-likelihood ratio based on the (independent) binomial distributions of F1 (t 1 ), P2 (t 1 , t 2 ) and F3 (t 2 ). This provides a further justification for the result in Theorem 2.1 under the considered weak conditions, which do not even involve the continuity of F 1 , F 2 and F 3 .…”
Section: Three-sample El and Confidence Regions For Triplets Of Tcfsmentioning
confidence: 68%
“…Observe that, in (5), each of the three addenda is an EL pivot (with approximant distribution đťś’ 2 1 ) for inference about an unknown proportion or probability, estimated by its empirical counterpart; in a sample of independent and identically distributed observations, such empirical counterpart, multiplied by the sample size, is the realization of a binomial random variable.…”
Section: Confidence Intervals For the Vusmentioning
confidence: 99%
See 1 more Smart Citation
“…However, when the dimension d of the covariate X diverges, it can be shown that the estimator in ( 8 ) is no longer consistent with the true parameter β 0 , and the estimation equation is no longer robust [ 16 ], which leads to the model prediction will have serious error accumulation and reduces the prediction accuracy [ 16 , 61 ]. Hence, to solve these problems, we introduce a class of penalty function mentioned in Liu et al (2023) [ 21 ] as follows, …”
Section: Methodsmentioning
confidence: 99%
“…Concretely, we begin by defining the Îł -divergence and introducing a class of penalty function mentioned in Liu et al (2023) [ 21 ], which yields the objective function Eq (9) . Based on this, we derive the consistency and efficiency of our model parameter estimation (refer to Theorems 1 and 2), as well as the empirical risk upper bound of our model (refer to Theorem 3).…”
Section: Introductionmentioning
confidence: 99%